Introducing body theology - Isherwood, Lisa (Introductions in feminist theology, 1998)
This book sets out to examine the ambiguous relationship that Christianity has with the body. Incarnation is central to Christian belief but that doctrine has not encouraged a positive theology of the body. The authors explore why this has been so and examine ways in which a more body-positive theology can be developed using our Christian heritage. Starting from a feminist perspective they reclaim women's bodies from the embrace of patriarchy and in doing so clearly show how this reclamation challenges many systems of oppression. This work illustrates that the personal is political, even in th.